Kristijan Milić: The Living and the Dead (Živi i mrtvi, 2007) - Gilić, Nikica (Array, 2012)
Kristijan Milić's "Alive and the Dead" is a film of intriguing structure and vision of history, of the relationship of different historical periods. Also, it is a film of great stylistic and artistic value in the context of Croatian and European cinema, with its mixture of neo-American genre poetics with the poetics of European art cinema.